2008
DOI: 10.1017/s1355617708080508
|View full text |Cite
|
Sign up to set email alerts
|

Oralmotor slowing in multiple sclerosis: Relationship to neuropsychological tasks requiring an oral response

Abstract: Although most neuropsychological batteries used with multiple sclerosis (MS) patients now exclude tests that require significant motor writing or manual manipulation speed, many of the most sensitive commonly used cognitive tests nonetheless require some type of rapid oral motor response. The aim of this study is to examine the extent to which primary oral motor articulation speed problems of individuals with MS contribute to performance and group differences on neuropsychological tasks requiring a rapid spoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…When DDK rate was statistically controlled, cognitive test scores for persons with MS and healthy controls became more similar. Similar findings were reported by Arnett, Smith, Barwick, Benedict, and Ahlstrom (2008). Although these studies seem to suggest that speech motor impairment may contribute to the appearance of cognitive impairment in MS, the use of DDK in this study should be considered carefully (Westbury & Dembowski, 1993).…”
Section: Introductionsupporting
confidence: 83%
“…When DDK rate was statistically controlled, cognitive test scores for persons with MS and healthy controls became more similar. Similar findings were reported by Arnett, Smith, Barwick, Benedict, and Ahlstrom (2008). Although these studies seem to suggest that speech motor impairment may contribute to the appearance of cognitive impairment in MS, the use of DDK in this study should be considered carefully (Westbury & Dembowski, 1993).…”
Section: Introductionsupporting
confidence: 83%
“…These include a reliance on oral responses, which if impaired can slow performance [36], and good visual acuity, for even mild impairments can also affect the results [37]. Reliance on oral responses may also produce motion artefacts when applied to fMRI studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the MACFIMS tests require a rapid Multisyllabic Combinations (MRRSMC) requires examinees to repeat the phonemes 'pa' 'ta' or 'ka' as quickly as possible in one good breath lasting at least 6 s. The number of syllables per second is the main scoring index. Slowed speech measured by this task has been demonstrated to be associated with performance on several of the tasks in the MACFIMS requiring a rapid spoken response, including the COWAT, Animal Naming, PASAT and Oral Symbol Digit [30]. Finally, screening for fatigue using the Fatigue Impact Scale is a recommended supplement to the MACFIMS.…”
Section: Measurement Of Cognitive Functioningmentioning
confidence: 99%
“…In addition, because fluency tasks require the rapid production of information, patients may perform poorly on them because of speeded-processing deficits. Slowed speech, common to MS, may also play a role in performance on such tasks, something that at least two recent studies have demonstrated [29,30]. Approximately 20-25% of patients have substantial problems on verbal fluency tasks [18], although some studies have reported impairment frequencies lower than 15% [5].…”
Section: Nature Of Deficits Seen In Msmentioning
confidence: 99%